New Developments in Madrassa Education: A Comparison of Project-Based Learning Approaches at Minhaj-Ul-Quran and Jamia-Tul-Rashid - Khan Raja Hammad; Sadheer Khan Bin Tofique ur Rahman (Mufti Muhammad Hassan); Dr. Ahmad El-Muhammady, Bin Muhammad Uthman El-Muhammady (`, 2026)
In Pakistan, discussions about reforming madrassas often focus more on state regulation and curriculum content than on pedagogy. To fill that gap, this article compares two reformist madrassas that have led the way in fusing traditional Islamic studies with contemporary subjects and project-based learning (PBL): Jamia-tul-Rashid in Karachi and Minhaj-ul-Quran in Lahore. Utilising Primary research, observation and field work along with secondary research, institutional documents, and publicly accessible materials, the study investigates each institution’s conception and application of student-centered learning. Minhaj-ul-Quran places greater emphasis on leadership development, civic engagement, and international networks than Jamia-tul-Rashid does on market-readiness through exposure to finance, management, and applied research. Both institutions demonstrate how PBL can improve Islamic pedagogy while remaining true to tradition, despite their differing approaches. This article examines constructivist methods for combining modern and traditional education in Pakistani madrassas as part of a larger doctoral research project at the International Institute of Islamic Thought and Civilisation (ISTAC-IIUM). The article adds to the body of knowledge on Islamic education reform by placing these two cases within that larger framework. It also provides design guidelines that other madrassas could use to address modern issues. Keywords: Madrassa Education, Project-Based Learning (PBL), Islamic Pedagogy, Educational Reform, Constructivist Methods, Minhaj-ul-Quran, and Jamia-tul-Rashid. https://doi.org/10.5281/zenodo.19494240